Differential Effects of Methoxy Group on the Interaction of Curcuminoids with Two Major Ligand Binding Sites of Human Serum Albumin - Sato, H.; Chuang, Victor; Yamasaki, K.; Yamaotsu, N.; Watanabe, H.; Nagumo, K.; Anraku, M.; Kadowaki, D.; Ishima, Y.; Hirono, S.; Otagiri, M.; Maruyama, T. (Public Library of Science, 2014)
Curcuminoids are a group of compounds with a similar chemical backbone structure but containing different numbers of methoxy groups that have therapeutic potential due to their anti-inflammatory and anti-oxidant properties. They mainly bind to albumin in plasma. These findings influence their body disposition and biological activities. Spectroscopic analysis using site specific probes on human serum albumin (HSA) clearly indicated that curcumin (Cur), demethylcurcumin (Dmc) and bisdemethoxycurcumin (Bdmc) bind to both Site I (sub-site Ia and Ib) and Site II on HSA. At pH 7.4, the binding constants for Site I were relatively comparable between curcuminoids, while the binding constants for Site II at pH 7.4 were increased in order Cur , Dmc , Bdmc. Binding experiments using HSA mutants showed that Trp214 and Arg218 at Site I, and Tyr411 and Arg410 at Site II are involved in the binding of curcuminoids. The molecular docking of all curcuminoids to the Site I pocket showed that curcuminoids stacked with Phe211 and Trp214, and interacted with hydrophobic and aromatic amino acid residues. In contrast, each curcuminoid interacted with Site II in a different manner depending whether a methoxy group was present or absent. A detailed analysis of curcuminoids-albumin interactions would provide valuable information in terms of understanding the pharmacokinetics and the biological activities of this class of compounds.